Association between schizophrenia and homozygosity at the dopamine D3 receptor gene. - Crocq, M A (1992)
Disturbances in dopamine neurotransmission have been postulated to underlie schizophrenia. We report data from two independent studies of a BalI polymorphism in the dopamine D3 receptor gene in patients with schizophrenia. In both studies, more patients than controls were homozygous (p = 0.005, p = 0.008). When pooled data were analysed, this difference was highly significant (p = 0.0001) with a relative risk of schizophrenia in homozygotes of 2.61 (95% confidence intervals 1.60-4.26).